Internalization of Islamic Educational Values in The Ngapati Tradition in Gondang Village Karangreja District, Purbalingga District - Hasan, Masrur; Fadilah, Isnaeni; Misbah, Muhammad (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This study aims to find out how the Ngapati tradition is carried out by the community in Gondang Village, Karangreja District, Purbalingga Regency, and to find out how the Internalization of Islamic Education Values in the community in the Ngapati tradition in Gondang Village, Karangreja District, Purbalingga Regency. This type of research is field research where researchers go directly to the field to obtain data and information related to the research being conducted. This research is presented in a descriptive form to describe a process that occurs in the field. While the approach taken is qualitative. Data collection techniques used: observation, interviews, and documentation. While the data analysis technique uses three steps of data analysis: Data Reduction, Data Presentation, and Drawing Conclusions. The results showed the internalization of Islamic Education's values in the Ngapati tradition in Gondang Village, Karangreja District, Purbalingga Regency. The implementation of the Ngapati tradition in Gondang Village, Karangreja District, Purbalingga Regency, has two phases. Namely the pre-event phase of the Ngapati tradition and the event at the time of carrying out the Ngapati tradition. The processes within are internalized with general procedures which include three internalization stages: Value Transformation, Value Transactions, and Value Transinternalization